Charlemagne in medieval German and Dutch literature - Classen, Albrecht 1956- (D. S. Brewer, 2021)
Comprehensive survey of the legend of Charlemagne in the medieval German-speaking world
Keywords: Karl -- I. -- Heiliges Römisches Reich, Kaiser -- 747-814; Mittelhochdeutsch; Literatur; Literarische Gestalt; Mittelniederländisch; Charlemagne / Emperor / 742-814 / In literature; German literature / Middle High German, 1050-1500 / History and criticism; Dutch literature / To 1500 / History and criticism; Charlemagne / Emperor / 742-814; Dutch literature; German literature / Middle High German; Literature; To 1500; Criticism, interpretation, etc